DIGITALIZATION OF HR TECHNOLOGIES AND ANTI-CRISIS MANAGEMENT OF ENTERPRISES UNDER CONDITIONS OF MILITARY TURBULENCE - Mazur, Nataliya (МІЖНАРОДНА ЕКОНОМІКА В УМОВАХ КЛІМАТИЧНИХ ЗМІН: ГЛОБАЛЬНІ ВИКЛИКИ, 2026)
.